2012
DOI: 10.1074/jbc.m111.336511
|View full text |Cite
|
Sign up to set email alerts
|

The Kv7.2/Kv7.3 Heterotetramer Assembles with a Random Subunit Arrangement

Abstract: Background: Kv7.2 and Kv7.3 coassemble to form a heteromeric K ϩ channel that generates the M-current.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 34 publications
1
22
0
Order By: Relevance
“…This mutation at the first position of the selectivity filter signature (GYG) exerts a dominant‐negative effect . Accordingly, no currents were observed when combined with Kv7.3, but when expressed with both Kv7.2 and Kv7.3, current levels were recovered, which, taking into account the random assembly of subunits, suggest that the incorporation of 2 mutated subunits is required to abolish current in Kv7.2/Kv7.3 heterotetramers. Similarly, the E130K mutant exerted a dominant‐negative effect with Kv7.2, but not when expressed with Kv7.2 and Kv7.3.…”
Section: Discussionmentioning
confidence: 99%
“…This mutation at the first position of the selectivity filter signature (GYG) exerts a dominant‐negative effect . Accordingly, no currents were observed when combined with Kv7.3, but when expressed with both Kv7.2 and Kv7.3, current levels were recovered, which, taking into account the random assembly of subunits, suggest that the incorporation of 2 mutated subunits is required to abolish current in Kv7.2/Kv7.3 heterotetramers. Similarly, the E130K mutant exerted a dominant‐negative effect with Kv7.2, but not when expressed with Kv7.2 and Kv7.3.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of a variety of channels and receptors have shown that subunit arrangement in the conformation of heterooligomers varies depending on which membrane protein is being analyzed. It has been proposed that individual proteins might assemble with a random arrangement that is dependent on their abundance (40)(41)(42)(43), with a random arrangement of preformed homomeric dimers (44), and some channels even assemble as heteromeric structures with fixed stoichiometry (45,46). With respect to aquaporins, it was reported that the AQP4 isoforms M1 and M23 seem to assemble as heterotetramers with a random arrangement (47).…”
Section: Discussionmentioning
confidence: 99%
“…A fixed stoichiometry and subunit arrangement have been reported for transient receptor potential channels, where the co-expression of TRPP (polycystin) (TRPP2) and TRPC (canonical) (TRPC1) subunits formed heteromeric channels with a 2 : 2 stoichiometry and subunits arranged alternately within the tetramer (Kobori et al, 2009;Stewart et al, 2010). In contrast, it has been proposed that heteromeric KCNQ (Kv7) channels display variable stoichiometry, with subunits arranged randomly (Stewart et al, 2012). These data indicate that a fixed stoichiometry and arrangement of subunits within a channel tetramer might be common and would suggest that the diversity of potassium and other channels might not be as large as originally thought (Jan & Jan, 1990).…”
Section: Discussionmentioning
confidence: 99%